The Effectiveness of a Proposed Educational Program Based on Nelson and Narnes Theory in Improving Chemistry Achievement among Second Intermediate School Students (Journal of the College of Basic Education, 2026)
The present study aims to investigate the effectiveness of a proposed instructional program based on the Wilson and Narens theory in improving chemistry achievement among second-grade intermediate school students. To achieve the objective of the study, the researcher adopted an experimental research design to test the following null hypothesis:There is no statistically significant difference at the (0.05) level between the mean achievement scores of students in the experimental group who study chemistry using the instructional program developed according to the Wilson and Narens theory and the mean achievement scores of students in the control group who study chemistry using the conventional instructional method in the post-test. The two groups were equated in several variables, including chronological age, prior academic achievement, and intelligence test scores. A total of (97) behavioral objectives were formulated and distributed across the following cognitive levels of Bloom’s taxonomy: knowledge, comprehension, and application.The experimental group was taught according to the Wilson and Narens instructional program, which consists of four stages: planning, analysis, design, implementation, and evaluation, during the first semester of the academic year (2024–2025). The researcher developed an achievement test consisting of (20) objective multiple-choice items.The results of the study revealed that students in the experimental group who studied chemistry using the instructional program based on the Wilson and Narens theory outperformed students in the control group who studied chemistry using the conventional method in the achievement test. Based on the findings.